2000
DOI: 10.1038/35015073
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive force of a single gecko foot-hair

Abstract: Geckos are exceptional in their ability to climb rapidly up smooth vertical surfaces. Microscopy has shown that a gecko's foot has nearly five hundred thousand keratinous hairs or setae. Each 30-130 microm long seta is only one-tenth the diameter of a human hair and contains hundreds of projections terminating in 0.2-0.5 microm spatula-shaped structures. After nearly a century of anatomical description, here we report the first direct measurements of single setal force by using a two-dimensional micro-electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

48
2,180
2
18

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,489 publications
(2,248 citation statements)
references
References 11 publications
48
2,180
2
18
Order By: Relevance
“…[1][2][3][4][5] Among the many functions imparted by fibrous structures, their wettability at both the micro-and macro-scale is very important because it can facilitate or even determine the manner in which organisms interact with the surrounding environment. [4][5][6] As our recent studies revealed, the spider silk with unique periodic spindleknot and joints can harvest water from humid air, 4 certain cactus species with conical spines can efficiently collect fog 5 and certain fish with anisotropic hook-like spines exhibit self-cleaning under water.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among the many functions imparted by fibrous structures, their wettability at both the micro-and macro-scale is very important because it can facilitate or even determine the manner in which organisms interact with the surrounding environment. [4][5][6] As our recent studies revealed, the spider silk with unique periodic spindleknot and joints can harvest water from humid air, 4 certain cactus species with conical spines can efficiently collect fog 5 and certain fish with anisotropic hook-like spines exhibit self-cleaning under water.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, peeling is an interesting and ubiquitous process in biological and artificial adhesive systems. For example, peeling is important in the attachment and detachment processes of artificial tapes used to fix objects and biological adhesive systems including ants, bees, flies, cockroaches, geckos, frogs, and so on 2, 8, 19, 20, 21, 22, 48. Peeling is also an important phenomenon in many applications, such as paint and coating technology, cell adhesion, and transfer printing 23, 30, 48.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is the ability to combine exceptional strength and toughness, which occurs for example in nacre, bone and dentine (Espinosa et al, 2011;Pugno, 2006;Wegst and Ashby, 2004), or the smart adhesion which is found in spiders and geckos (Autumn et al, 2000; and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 growth (Cranford and Buehler, 2011).…”
Section: Introductionmentioning
confidence: 99%